A detailed taxonomic study on two new and one known species of Anaplectus De Coninck & Schuurmans Stekhoven, 1933 (Nematoda: Plectidae) - Jahan, Rehmat; Khan, Rahmat; Mahboob, Mohammad; Tahseen, Qudsia (Zootaxa, 2020)
This paper provides descriptions of two new and one known species of the genus Anaplectus De Coninck & Schuurmans Stekhoven, 1933. Anaplectus sudhausi sp. nov. is characterised by leaf-shaped lips interspersed with interlabial liplets; bifid apices of the lateral lips; cheilostom with non-cuticularised walls; gymnostom with cuticularised arcuate walls; 120–132 sublateral hypodermal glands on each body side with an additional 5–8 smaller subdorsal hypodermal glands; female tail with three caudal setae; males with arcuate spicules having manubrium slightly wider than calomus or blade, last median tubulus or supplement about half the spicule length and tail terminus with a weakly cuticularised spinneret. A. labiosulcus sp. nov. is characterised by 115–123 sublateral hypodermal glands on each side of the body with those on the dorsal side usually larger than the ventrals; the 5–6 anteriormost glands are unpaired and arranged linearly; lips with cuticularised interlabial grooves; gymnostom arched, occasionally double-arched and caudal glands grouped and opening through a cuticularised spinneret. A. granulosus (Bastian, 1865) De Coninck & Schuurmans Stekhoven, 1933 has been redescribed with some minor differences from previous descriptions.